"We Aren't Here to Win; We are Here Not to Lose": Emergency Physicians' Communicative Management of Uncertainty. Issue 6 (12th May 2023) - Miller, Laura E.; Woo, Dajung
ABSTRACT: Healthcare providers in hospital emergency departments (EDs) work under high uncertainty and pressure to manage a variety of patients efficiently. Whereas much existing research has examined communicative implications of uncertainty from patients' perspectives, we explored ED physicians' experiences of uncertainty in their everyday work environment. Through an ethnographic fieldwork in an ED, we identified three main sources of uncertainty routinely faced by physicians: (a) patients' incorrect expectation about the role of ED; (b); patient variability and ED physicians' breadth of expertise; and (c) emerging and unexpected changes in patient cases after handoffs. We also found how ED physicians managed these uncertainties, including: (1) direct admission of scientific uncertainty to patients; (2) lowering epistemic uncertainty through swift Internet searches; and (3) maintenance of situational uncertainty. We discuss implications of these findings for researchers, providers, and hospital organizations.